2020
DOI: 10.1111/1756-185x.13840
|View full text |Cite
|
Sign up to set email alerts
|

High levels of cathepsin S and cystatin C in patients with fibromyalgia syndrome

Abstract: Fibromyalgia syndrome (FM) is a musculoskeletal disease characterized by chronic diffuse pain and increased pain sensitivity. 1 Although the etiopathogenesis of FM is not yet clear, genetic, environmental and immunological factors, and peripheral and central mechanisms are thought to play a role. 2 In clinical studies, central sensitization has been thought to be responsible for the pathogenesis of FM and it has been claimed that abnormalities in the perception and/or processing of pain in the central nervous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
1
6
0
1
Order By: Relevance
“…The LOD achieved with our sensor is the lowest value com-paring with earlier reports under neutral pH. Further, Pt TPs/GC electrode possess higher catalytic activity than the platinum NPs [49] and other platinum NPs based composite materials for hydrazine. [50,69,70] Selectivity of the sensor towards hydrazine was tested in the presence of variety of biological important mole-cules such as dopamine, ascorbic acid, glucose, uric acid and H 2 O 2 (100 folded excess) and some common ions Na + , NH 4 + , Ca 2 + , NO 2 À , Zn 2 + , K + , Co 2 + and Ni 2 + (500-fold excess) using amperometry technique (Figure 4c).…”
supporting
confidence: 75%
“…The LOD achieved with our sensor is the lowest value com-paring with earlier reports under neutral pH. Further, Pt TPs/GC electrode possess higher catalytic activity than the platinum NPs [49] and other platinum NPs based composite materials for hydrazine. [50,69,70] Selectivity of the sensor towards hydrazine was tested in the presence of variety of biological important mole-cules such as dopamine, ascorbic acid, glucose, uric acid and H 2 O 2 (100 folded excess) and some common ions Na + , NH 4 + , Ca 2 + , NO 2 À , Zn 2 + , K + , Co 2 + and Ni 2 + (500-fold excess) using amperometry technique (Figure 4c).…”
supporting
confidence: 75%
“…The pain characteristics also can be variable since they are affected by several distinct factors, such as physical or mental stress, comorbidities, and temperature 1 , 3 , 4 . Besides, although widespread pain is the most common manifestation, patients with the disease also can experience symptoms involving almost all body systems, such as cognitive dysfunction, dyspepsia, and urinary tract disorders, besides other signs that can be difficult to distinguish between other chronic conditions 1 , 4 , 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Fibromyalgia Syndrome (FM) is a chronic musculoskeletal system disease characterized by widespread pain and high levels of sensitivity to pain (1). The pathogenesis of FM has not been fully clarified as yet, but environmental, genetic and immunological factors, as well as central and peripheral mechanisms, are thought to have a role in the pathogenesis (2). Previous studies have attributed FM pathogenesis to central sensitization, suggesting that the central nervous system (CNS) may have a role when there are abnormalities in the processing and/or perception of pain (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…Central sensitization is defined as the erroneous and abnormal response of the CNS to a peripheral stimulus due to neuronal hyperexcitability and hypersensitivity in the central nervous (5). Some chemokines, cytokines and neuromodulators are known to function during postsynaptic and presynaptic processing of a peripheral nociceptive stimulus in the CNS (2). It has been suggested that hyperalgesia and allodynia develop due to increases or inhibition loss in membrane excitability and synaptic activity through reductions or increases in the inhibitor and excitatory neurotransmitters (3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%